Redescription of the deep-sea colonial ascidian Synoicum molle (Herdman, 1886): First record since its original finding during the Challenger Expedition - Maggioni, Tamara (2016)
The colonial ascidian Synoicum molle (Herdman, 1886) was recorded for the first time after its original description. The slope area where S. molle was discovered during the Challenger Expedition (1872-1876), located at the mouth off Río de La Plata (Argentine Sea), still remains highly underexplored. During a series of deep-sea prospections along the SW Atlantic (A.R.A. Puerto Deseado, August 2012), 7 colonies of S. molle were collected few km from the type locality. The finding permitted to perform, for the first time, a complete morphological description of this species. The proper identification of marine species, especially deep-sea organisms, has implications for the general knowledge of biodiversity, a necessary tool for the conservation and study of ecosystem benefits that marine environments provide.